2021
DOI: 10.1021/acssensors.1c00050
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Microfluidic Sample Homogeneity and Improved Antibody-Based Assay Kinetics Due to Magnetic Mixing

Abstract: Recent global events have distinctly demonstrated the need for fast diagnostic analysis of targets in a liquid sample. However, microfluidic lab-on-a-chip devices for point-of-care diagnostics can suffer from slow analysis due to poor mixing. Here, we experimentally explore the mixing effect within a microfluidic chamber, as obtained from superparamagnetic beads exposed to an out-of-plane (vertical) rotating magnetic field. Various magnetic protocols are explored, and the level of sample homogeneity is measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…68 A specific example is the need for mixing in confined micro-reaction chambers of point-of-care devices in order to enhance the speed and reproducibility of diagnostic testing; 69 artificial cilia can potentially provide this function since they operate at the right length scale and they offer a fully integrated solution. 70 However, fluid transport and mixing by cilia in confined spaces have not attracted much attention. Recently, we analyzed the fluid transport in a confined channel by pneumatic artificial cilia submerged in a viscous fluid and actuated by trapezoidal pressure waves using a combination of experiments and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…68 A specific example is the need for mixing in confined micro-reaction chambers of point-of-care devices in order to enhance the speed and reproducibility of diagnostic testing; 69 artificial cilia can potentially provide this function since they operate at the right length scale and they offer a fully integrated solution. 70 However, fluid transport and mixing by cilia in confined spaces have not attracted much attention. Recently, we analyzed the fluid transport in a confined channel by pneumatic artificial cilia submerged in a viscous fluid and actuated by trapezoidal pressure waves using a combination of experiments and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…(i) The basic modes of magnetic bead motion in the absence and presence of a magnetic field and magnetic gradients and the relevant forces. Image adapted from (Shanko et al 2021) (ii) Schematic of the working principle of mushrooms in a circular array around the chamber circumference of a microfluidic chip, and when applying an inplane counterclockwise rotating external magnetic field. Only half of the chamber is shown here (color figure online) disk like structures (Nagaoka et al 2005).…”
Section: Theory Of Magnetic Bead Dynamicsmentioning
confidence: 99%
“…Recently, we have shown that applying an out-of-plane rotating magnetic field can induce global swarming of magnetic microbeads in a circular microfluidic chamber, leading to chaotic fluid flow and effective mixing (Shanko et al 2021).We found that under certain conditions, increased fluid kinetics due to the motion of the magnetic beads contribute to faster and more efficient immunoassay sensing. However, an out-of-plane configuration will hinder optical visualization.…”
Section: Introductionmentioning
confidence: 95%
“…40 Herein, we have sought to control the collective motion of magnetic immunoparticles through the use of alternating (AC) magnetic fields, generated by off-the-shelf electromagnets, spanning simple-printed microfluidic channels; we observe that this promotes capture efficiencies within a few tens of minutes, which are typically (otherwise) only achieved across many hours. 41 Magnetic field switching also promotes a controlled in situ exosome washing and lysing (Scheme 1A) prior to a dual marker α-syn and syntenin-1 (synt-1) electrochemical quantification at disposable 32-multielectrode arrays (Scheme 1B). The entire methodology was validated through the analysis of 72 patient samples, with a resolved strong statistical correlation between α-syn expression in neuronal (L1CAM+) exosome and PD status.…”
Section: ■ Introductionmentioning
confidence: 99%